AKTIVITAS ENZIM PENCERNAAN UDANG VANAME (Penaeus vannamei) YANG DIBERIKAN PAKAN BERBAHAN BAKU TEPUNG Skeletonema costatum - Dewi Putri Lestari (Jurnal Perikanan Unram, 2018)
The aim of this study was to investigate the effect of Skeletonema costatum meal utilization in various doses to substitute fish meal in shrimp diet (Penaeus vannamei) on activity of protease and amilase enzyme. Tested diets were formulated isoprotein of 37 % and iso energy of 3,6 kkal/g diet. The experiment used Completely Randomized Design with four treatments and three replications. The treatments were doses of skeletonema meal in order to substitute fish meal in diets. The doses of fish meal substitution by skeletonema meal were A = 0%; B 2,5%; C = 5%; and D 7,5%. The best dosage was determined by using regression analysis. The result of the experiment showed that enzyme activity of protease and amilase increased significantly during the experiment. The regression analysis show that the best dosage of skeletonema meal to subtitute fish meal in shrimp diets based on enzym activity were 4,07% for protease and 4,02% for amilase